Grounded Theory methods in child psychotherapy research. Issue 2 (3rd May 2016) - Rustin, Michael
Abstract : This article considers the place of qualitative research in psychoanalysis and child psychotherapy. It discusses why research methodology for many years occupied so small a place in these fields, and examines the cultural and social developments since the 1960s which have changed this situation, giving formal but also qualitative methods of research much greater significance. It reflects on the different pressures to develop explicit research methods which arise both from outside the psychoanalytic field, as a condition of its continued professional survival, and from within it, where its main aim is the development of fundamental psychoanalytic knowledge. It suggests that the conduct of mainly quantitative research into treatment outcomes is largely a response to these external pressures, whilst the main benefits to be gained from the development of qualitative research methods, such as Grounded Theory, are in facilitating the knowledge-generating capacities and achievements of child psychotherapists themselves. The paper describes Grounded Theory methods, and explains how they can be valuable in the recognition of hitherto unrecognised meanings and patterns as these are made visible in clinical practice. Finally, it briefly describes three examples of completed doctoral studies, all of which have added significantly to the knowledge-base of child psychotherapy, and which demonstrate how much can be accomplished using this method of research.